Adenoid cystic carcinoma of submandibular salivary gland: A case report with extensive management - P Venkatalakshmi Aparna; J Venkatesh; S Leena Sankari; N Narmatha (Wolters Kluwer Medknow Publications, 2021)
Adenoid cystic carcinoma (ACC) is a relatively rare epithelial malignant tumor of the major and minor salivary glands with deceptive benign histologic appearance characterized by indolent, locally invasive growth with a high propensity for local recurrence and distant metastasis. Typical ACC has a cribriform pattern, presenting a very aggressive course among the histologic variants. According to the Armed Forces Institute of Pathology (AFIP), ACC was considered the fifth most common malignant epithelial tumor of the salivary gland. ACC is more common in the minor salivary gland, the palate being the most common site, submandibular salivary gland and least followed by sublingual and parotid glands. ACC accounts for about 1% of all malignant tumors of the oral and maxillofacial regions. Thus, considering its rarity, we would like to discuss a case report of ACC of the submandibular salivary gland in a 52-year-old female patient with a typical histological pattern, which would epitomize all cases of ACC along with extensive management.